Effects of public participation on environmental governance in China: A spatial Durbin econometric analysis. (25th October 2021) - Ge, Tao; Hao, Xionglei; Li, Jinye
Abstract: Industrial pollution caused by China's rapid urbanization and industrialization is a serious threat to the ecological environment and human health, which stimulates public appeals for better environmental quality and public participation in regional environmental governance. Hence, using panel data of 30 Chinese provinces during 1999–2015, this study explores the effect of public participation on environmental governance based on the spatial Durbin econometric model. The results reveal that there is a negative spatial correlation in environmental governance among regions, that is, the increase in environmental governance in one region reduces the environmental governance in neighboring regions. Meanwhile, public participation has positive local and spillover effects on expenditure-based and revenue-based environmental governance, which promotes environmental governance expenditures and benefits in local and neighboring areas. However, the spatial spillover effect of public participation on environmental governance is only significant within 900 km and decreases with increasing geographic distance within this range. In addition, the roles of public behavior participation and public policy participation on environmental governance are mutually replaceable, and the improvement of the other can strengthen local and spillover effects of public participation on environmental governance when one of them remains unchanged. To achieve high-quality green development, the Chinese government should broaden the channels for public participation in environmental governance, improve the environmental protection assessment system, and deepen cross-regional pollution control cooperation mechanisms. Graphical abstract: Image 1 Highlights: China's 30 provinces have negative spatial correlation in environmental governance. Public participation promotes environmental governance expenditures and benefits. Local public participation improves environmental governance in neighboring areas. The spillover effect of public participation is significant within 900 km. Public behavior participation and policy participation are mutually replaceable.